Case Report: A Case Series Linked to Vitamin D Excess in Pet Food: Cholecalciferol (Vitamin D3) Toxicity Observed in Five Cats - Vecchiato, Carla G.; Delsante, Costanza; Galiazzo, Giorgia; Perfetti, Simone; Pinna, Carlo; Sabetti, Maria C.; Zagnoli, Laura; Biagi, Giacomo; Pietra, Marco (Frontiers in Veterinary Science, 2021)
Cholecalciferol (vitamin D3) toxicity caused by defective pet food formulations is a rare occurrence described in cats. Nevertheless, it poses a health risk, even though the affected pet food is not fed as the sole diet. Excessive vitamin D3 intake might cause hypercalcemia and soft tissue mineralization, which are findings that prompt clinicians to further investigate the feasible etiology. This case series describes the effects of an extremely high vitamin D3 intake in five young cats caused by the consumption of a fish-based complementary kitten pet food (KPF) that was fed to all of the cats as part of their diet (cases 1, 2, and 3) or eaten exclusively (cases 4 and 5). Due to the different amounts of vitamin D3 consumed, diagnostic examinations showed different degrees of severity of hypercalcemia and azotemia as well as different radiographic findings in cases where diagnostic imaging was performed (cases 2, 4, and 5). All of the cats were treated by withdrawing the affected food and providing medical management of the hypercalcemia. All of the cats recovered, except for two persistent azotemic cats, which developed chronic kidney disease. The goal of this case series is, therefore, to describe the occurrence and resolution of an acute vitamin D3 toxicity due to the highest amount of dietary vitamin D3 intake that has ever been described in domestic cats.